KONSELING INDIVIDUAL PESERTA DIDIK BERKESULITAN BELAJAR DAN PENGENTASAN MELALUI STRATEGI PEKERJAAN RUMAH DAN FONIK - Elpiani Rambe; Bukhari Is (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2022)
This study aims to reveal a number of learning difficulties for grade 3 of students at Sekolah Dasar Negeri (SDN) Balirejo Yogyakarta. They have difficulty learning based on symptoms that appear when learning. This research type is a field research using a qualitative research to the type of case study. The results revealed that the types of learning difficulties of students (based on information from homeroom teachers and subject teachers) were lazy to learn, slow in understanding questions, slow in writing and reading. After the researchers conduct counseling, provide exercises in the form of text and based on the theory the researcher reads, the learning difficulties of students include the slow learner types and selections. The results of individual counseling indicate that there are changes and progress in student learning. By carrying out individual counseling and alleviation solutions through homework and phonics strategies, students/counselees more easily understand each question, more diligently coming to school, better understanding how to read correctly and write neatly and correctly. The counseling phase conducted by researchers starts from the planning, implementation, evaluation, follow-up stages and reports on counseling results.